2021
DOI: 10.23917/varidika.v33i1.13200
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Kegiatan Literasi Dalam Meningkatkan Minat Baca Peserta Didik Di Sekolah Dasar

Abstract: Penelitian merupakan penelitian kepustakaan (library research). Pengumpulan data dengan menggunakan dokumentasi, dari jurnal-jurnal penelitian. Analisis data dilakukan dengan menggunakan analisis analisis isi (content analysis). Strategi literasi di sekolah dasar dalam meningkatan minat baca, pada tahap pembiasan adalah melaksanakan membaca 15 menit sebelum mata pelajaran di mulai, membuat pojok baca, dan menciptakan lingkungan kaya teks. Pada tahap pengembangan, dengan mengadakan jam wajib berkunjung ke perpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 1 publication
1
11
0
14
Order By: Relevance
“…According to UNESCO data, the reading interest of the Indonesian people is very concerning, only 0.001%. This means that out of 1,000 Indonesians, only 1 person is an avid reader (Muslim et al, 2021;Sukma & Sekarwidi, 2021;Iqra, 2019). P.Kemdikbud (Tahmidaten & Krismanto, 2020) stated that the results of the Indonesia National Assessment Program in 2016 conducted by the Education Research Center (Puspendik) of the Ministry of Education & Culture itself revealed data that the national average distribution of literacy on the reading ability of students in Indonesia was 46.83% are in the Less category, only 6.06 are in the Good category, and 47.11 are in the Enough category.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to UNESCO data, the reading interest of the Indonesian people is very concerning, only 0.001%. This means that out of 1,000 Indonesians, only 1 person is an avid reader (Muslim et al, 2021;Sukma & Sekarwidi, 2021;Iqra, 2019). P.Kemdikbud (Tahmidaten & Krismanto, 2020) stated that the results of the Indonesia National Assessment Program in 2016 conducted by the Education Research Center (Puspendik) of the Ministry of Education & Culture itself revealed data that the national average distribution of literacy on the reading ability of students in Indonesia was 46.83% are in the Less category, only 6.06 are in the Good category, and 47.11 are in the Enough category.…”
Section: Introductionmentioning
confidence: 99%
“…P.Kemdikbud (Tahmidaten & Krismanto, 2020) stated that the results of the Indonesia National Assessment Program in 2016 conducted by the Education Research Center (Puspendik) of the Ministry of Education & Culture itself revealed data that the national average distribution of literacy on the reading ability of students in Indonesia was 46.83% are in the Less category, only 6.06 are in the Good category, and 47.11 are in the Enough category. In order for a reading culture to be formed in society, it is necessary to continuously develop interest in reading (Sukma & Sekarwidi, 2021) . Umar (2013: 127; Gol A; Gong & Agus M. Irkham 2012: 62) says that reading culture is an act of reading that is carried out repeatedly, continuously and continuously and has become part of a person's daily life (Sulistyo , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Learning strategies must be able to develop all aspects of student personality in an integrated manner. Using the discussion method, for example, lecturers must be able to design strategies for carrying out discussions that are not only limited to developing intellectual aspects, but must encourage students to develop as a whole (Sukma, 2020). Encouraging students to be able to respect the opinions of others, encouraging students to be brave in expressing ideas or ideas, encouraging students to be honest, about feelings, and so on.…”
Section: Lecturer's Strategy In Fostering Student Religious Charactermentioning
confidence: 99%
“…Students' interest in reading will not run by itself, but there is a need for self-awareness, habits, and practice consistently to read and the role of the teacher to encourage students to read. And this is inseparable from the quantity and quality of the reading material-external factors such as school and family environment [29] . The school environment is one of the factors that can increase students' interest in reading.…”
Section: Obstacles and Inhibiting Factorsmentioning
confidence: 99%
“…This will certainly encourage students to be comfortable visiting often, whether just reading during free learning hours or break time. In addition, students will be able to find reading sources that support learning in class so that students' reading interest increases [29].…”
Section: Introductionmentioning
confidence: 99%